Cow’s endomitritis - MORAITIS (Σ. ΜΩΡΑΪΤΗΣ) S.; SARATSIS (Φ. ΣΑΡΑΤΣΗΣ) Ph. (Journal of the Hellenic Veterinary Medical Society, 2018)
Uterine infections are a major cause of economic loss to the cattle industry, with both short and long-term losses occurring. This paper reviews the etiology, pathogenesis and predisposing factors of endometritis, the clinical signs, the diagnosis, as well as the impact of the various treatments on the fertility status of the cow.